Communicable illness mitigation strategies for traveling elite sporting organizations - McElheny, K. D.; Little, D.; Taylor, D.; Manzi, J. E. (Sports Health: A Multidisciplinary Approach, 2021)
Transmission of communicable diseases observed in sporting organizations is often preventable. Early detection, isolation, and treatment can significantly diminish time lost. Until recently, there has been a paucity of standardized guidelines outlining feasible, preventable measures to protect both athletes and staff from contagious illnesses. Therefore, the purpose of this narrative was to highlight optimal prevention practices for transmission mitigation, with a particular focus on hygiene activity and travel considerations in professional sporting organizations. Evidence Acquisition: Current recommendations from the Centers for Disease Control and Prevention and peer-reviewed journals. Study Design: Clinical review. Level of Evidence: Level 5. Results: Communicable illness prevention strategies begin at the level of sufficient personal hygiene practices. Common area surface cleaning recommendations, including shared equipment sanitization between usage as well as designated equipment use to specific athletes, should be considered to minimize cross-contamination, in particular, for liked-position players. Intelligent design for shared areas can include redistributing the layout of communal spaces, most feasibly, spreading locker designation a minimum distance of 6 ft from one another. Travel considerations can include placing most susceptible passengers closest to window seating, boarding last and exiting first. Team physicians should have knowledge of essential personnel medical histories in an effort to risk stratify staff members and players in the setting of communicable disease. Conclusion: Providing a framework for illness management and prevention is important when considering the effects on player health, missed time, performance, and overall cost. Containment of commonly observed communicable illnesses can be optimized with sufficient personal hygiene practices, common area surface cleaning recommendations, intelligent design for shared areas, travel and hotel considerations, as well as appropriate screening tools and isolation techniques. Strength of Recommendation Taxonomy (SORT): B.